2015
DOI: 10.1007/s10661-014-4222-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial assessment of water quality in the vicinity of Lake Alice National Wildlife Refuge, Upper Devils Lake Basin, North Dakota

Abstract: Runoff from concentrated animal feeding operations and croplands in the Upper Devils Lake Basin (Towner and Ramsey Counties), North Dakota, has the potential to impact the water quality and wildlife of the Lake Alice National Wildlife Refuge. Water samples were collected at eight locations upstream and downstream of the refuge, beginning in June 2007 through March 2011, to identify the spatial distribution of water quality parameters and assess the potential impacts from the upstream land use practices. Geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Understanding freshwater quality changes through space and time is important for sustainable use and exploitation of this finite resource and for anticipating future impact of land development on aquatic ecosystems. The interactions between LULC changes and stream integrity have been well documented [1][2][3][4][5]; previous studies have examined their impacts examined their impacts spatially [6][7][8][9] and temporally [8][9][10]. Specifically, studies have shown the highest instream sediment concentrations in agricultural areas [11,12], while correlations between instream nitrate concentrations and the proportion of agricultural and urban areas have been documented [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding freshwater quality changes through space and time is important for sustainable use and exploitation of this finite resource and for anticipating future impact of land development on aquatic ecosystems. The interactions between LULC changes and stream integrity have been well documented [1][2][3][4][5]; previous studies have examined their impacts examined their impacts spatially [6][7][8][9] and temporally [8][9][10]. Specifically, studies have shown the highest instream sediment concentrations in agricultural areas [11,12], while correlations between instream nitrate concentrations and the proportion of agricultural and urban areas have been documented [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The first and largest peak resulted from a mixture of rain and snow, and the next two resulted from rain, with the second being slightly larger than the first. It is possible that the slight surplus after 2011 was partially caused by backwash from the rise of Lake Irvine, which in 2015 started to drop (Vandeberg et al, 2015). The year 2016–2017 was a relatively dry year with a deficit that, unlike 2012, had a noticeable contribution from drift out, sublimation, and streamflow.…”
Section: Resultsmentioning
confidence: 99%
“…Precipitation peaked later in the summer of 2010, primarily in August (81.1 mm at Cando, and 166.4 mm at Rolla) and September (96.3 mm at Cando, and 144.6 mm at Rolla). High streamflow in the spring of 2011 was probably the main contributor, along with high precipitation, to the sharp rise of the lake level in Lake Irvine (Vandeberg et al, 2015). The year 2013 was also a flood year with a higher amount of precipitation than evapotranspiration leading to an increase in storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster analysis has proven useful when large, chemically complex datasets are evaluated (Kim et al, 2014). Identification of chemically similar water sources has been accomplished using hierarchical clustering (Flem et al, 2015; Hussain et al, 2008; Swanson et al, 2001; Vandeberg et al, 2015) and partition around medoids methods (Morrison et al, 2011). K-means clustering (Mandel et al, 2015), fuzzy clustering (Gentry, 2013; Güler and Thyne, 2004); and model-based clustering techniques have also been used (Kim et al, 2015; Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%